Psychological and Behavioral Factors Associated with Cyclic Vomiting Syndrome: Case Report - Sutarta, I. Putu Candra S.; Ardani, I. Gusti Ayu I.; Aryani, Luh Nyoman A.; Windiani, I. Gusti Ayu T.; Adnyana, I. Gusti Ngurah S.; Setiawati, Yunias (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction:Cyclic vomiting syndrome is a disorder of unknown etiology and pathogenesis characterized by recurrent and stereotypical vomiting episodes with varying intervals from baseline or normal health in between. The biopsychosocial model proposes that disease does not result from a single etiology but from systems that interact simultaneously at the cellular, tissue, organismal, interpersonal, and environmental levels. In addition, psychosocial factors have direct and reverse physiological and pathological consequences. Case: In this case report, A 17-year-old boy was consulted to the psychiatry department because of repeated vomiting suspected of psychological factors. The patient was hospitalized due to vomiting. This vomiting has been experienced by the patient since around 2 months before the examination. Patient’s father and stepmother actually really love this patient, but in the patient's perception, the patient's father and mother are less adequate in how to show their affection. The patient realized that his father loved him but felt in some ways, the patient was uncomfortable because he felt that he did not fit his father's mindset. Conclusion:The patient was diagnosed with Psychological and Behavioral Factors Associated with Cyclic Vomiting Syndrome (F54). Pharmacological therapy with 12.5 mg Amytriptiline tablet, 0.5 mg Risperidone tablet, and 5 mg Clobazam tablet every 24 hours orally (evening), while the non-pharmacological therapy given was supportive psychotherapy and psychoeducation to the parent.